Respuesta :

5x + y = 9....multiply by 7
10x - 7y = -18
----------------
35x + 7y = 63 (result of multiplying by 7)
10x - 7y = -18
----------------add
45x = 45
x = 45/45
x = 1

5x + y = 9
5(1) + y = 9
5 + y = 9
y = 9 - 5
y = 4

solution is : (1,4)
=========================
-4x + 9y = 9
x - 3y = -6 ....multiply by 4
----------------
-4x + 9y = 9
4x - 12y = -24 (result of multiplying by 4)
---------------add
- 3y = - 15
y = -15/-3
y = 5

x - 3y = -6
x - 3(5) = -6
x - 15 = -6
x = -6 + 15
x = 9

solution is : (9,5)
ACCESS MORE